The Role of Industry 5.0 in ESG-Based Talent Management Transformation at National Energy Companies - Kuswanto, Hary; Riyadi, Selamet; Iswati, Heni; Nugroho, Heru; Kusnawan, Agus (Maneggio, 2025)
This study aims to analyze the role of Industry 5.0 in driving the transformation of Environmental, Social, and Governance (ESG)-based talent management in national energy companies. The research method used is a qualitative approach with a case study strategy, through in-depth interviews, observations, and analysis of company documents related to HR policies and sustainability reports. The results show that Industry 5.0 contributes to building a more personalized, adaptive, and human-centered talent management system supported by intelligent technologies such as AI and big data. The integration of ESG in talent management further strengthens company sustainability, increases competitiveness, and builds employee loyalty. Despite challenges such as employee resistance, initial investment costs, and gaps in ESG understanding, strategic opportunities in the form of developing smart HR systems and data analytics are potential solutions. This study emphasizes the novelty of the integration of Industry 5.0, ESG, and talent management as a strategic framework for HR development in the national energy sector.